PENGARUH REMUNERASI DAN SEMANGAT KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KEJAKSAAN NEGERI MEDAN - Dito Aditia Darma Nasution (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2019)
This study aims to look at the effect of remuneration and work spirit on employee performance both partially and simultaneously at the Medan District Prosecutor's Office. The research used associative/correlation method. The population was 5 work units at the Medan District Prosecutor's Office consisting of Coaching, Pidum, Pidsus, Datun, and Intel work units and the sample of the study was 97 people including 18 employees in the Coaching work unit, 37 employees in the Pidum work unit, 18 people employees in the Pidsus work unit, 9 employees in the Datun work unit, and 15 employees in the Intel work unit. The data were primary data were obtained by using questionnaires and conducting a survey. The gathered data were analyzed by using multiple linear regression tests for analytical analysis which had been tested by using classic assumption test. The result of the research showed that, partially, Remuneration had positive and significant influence on the Employee Performance at the Medan District Prosecutor's Office and partially, Work Spirit had positive and significant influence on the Employee Performance at the Medan District Prosecutor's Office. Simultaneously, these results indicate that Remuneration and Work Spirit had significant influence on the employee performance at the Medan District Prosecutor's Office.